VD_FINDINFO HC / 2025 / 911 vom 24. November 2025 - VD Tribunal cantonal (2025)
ACTION EN DIVORCE, CAUSE DE DIVORCE, FORCE PROBANTE, CERTIFICAT MÉDICAL, MODIFICATION DE LA DEMANDE | 316 al. 1 CPC (CH), 317 al. 2 CPC (CH), 69 al. 1 CPC (CH)